Konsentrasi Tempe, Ikan, Tepung Havermout Pada Nugget Temfishmout Sebagai Snack Sehat Tinggi Protein, Rendah Lemak, Rendah Kolesterol Dan Tinggi Serat - Yunita Nazarena; Terati Terati; Eliza Eliza (Jurnal Pangan dan Gizi, 2023)
Background: Nuggets are a ready-to-eat and very popular. Frying five minutes, nuggets are ready to be consumed. Tempfishmout nuggets can diversify taste of nuget, increase economic value of tempeh, catfish and oatmeal as well as be beneficial health because the main ingredients contain nutrients. Research Objectives: determine the effect concentrations tempeh, catfish and havermout on the nutritional composition temfismout nuggets which contain low fat, high protein, low cholesterol and high fiber and it is hoped to diversification nuget taste, reducing the need for basic ingredients of chicken meat, increasing economic value and beneficial for health because the main ingredients contain nutrients. Methods: Research used a completely randomized design, 5 formulas with 3 replications. The frying method used is deep frying. Results: F1 Temfishmout Nuggets protein content (10.45%), Fat (12.77%), Cholesterol (2.58 mg/100g), Food Fiber (6.57%), F2 Temfishmout Nuggets protein content (10.42%) %), Fat (13.74%), Cholesterol (2.47 mg/100g), Dietary Fiber (7.61%), F3 Temfishmout Nuggets protein content (9.87%), Fat (13.22%), Cholesterol (7.07 mg/100g), Dietary Fiber (8.14%), F4 Nugget Temfishmout protein content (9.51%), Fat (9.31%), Cholesterol (6.74 mg/100g), Fiber Food (10.79%) and F5 Temfishmout Nuggets contain protein (10.71%), fat (9.26%), cholesterol (9.26 mg/100g), dietary fiber (7.90%).